The Earlier the Better? Pausing for Thought …. Issue 1 (20th October 2018) - Maughan, Barbara; Barker, Edward D.
Abstract : Is earlier intervention always superior? Using two complementary forms of meta‐analysis, Gardner and colleagues find no support for the "earlier is better" hypothesis in outcomes of parenting programs for child behavior problems across the 2–11 year age range. This commentary explores possible methodological and substantive reasons for the pattern of their findings. We need additional careful analyses of this kind, assessing age variations in intervention effects across broader age ranges, and in other developmental domains, for strong tests of the "earlier is better" hypothesis. At this stage, however, Gardner et al.'s findings give us some pause for thought.